TMOD-10. REPLICATION REPAIR DEFICIENT MOUSE MODELS PROVIDE INSIGHT ON HYPERMUTANT BRAIN TUMOURS AND COMBINATIONAL IMMUNOTHERAPY. (23rd April 2019) - Galati, Melissa; Bridge, Taylor; Sudhaman, Sumedha; Elshaer, Dana; Ercan, Ayse; Joksimovic, Lazar; Gams, Miki; Hodel, Karl; Lipman, Tatiana; Siddiqui, Iram; Borja, Richard de; Forster, Victoria; et al.
Abstract: Replication repair deficiency (RRD) is the leading cause of hypermutant brain tumours in children. RRD is caused by defects in one of four mismatch repair (MMR) genes— PMS2, MSH6, MLH1, and MSH2 —as well as mutations in the exonuclease "proofreading" domains of either DNA polymerase ε ( POLE ) or δ ( POLD1 ). Such tumours are often resistant to common therapeutic agents and animal models are needed to study RRD in vivo and test novel therapies like immune checkpoint inhibitors (ICIs). We initially engineered a Pole mutant mouse model harbouring the clinically relevant S459F mutation ( Pole S459F ). Pole S459F mice succumbed to various lethal cancers that mirrored the genomic landscape of POLE mutant human tumours. Pole S459F tumours were hypermutant (~170 mutations/Mb by whole exome sequencing), harboured mutational signature 10 (caused by POLE proofreading loss), and exhibited subclonal characteristics consistent with POLE -driven mutagenesis. Pole S459F tumours were not preventable by mono-ICI therapy and were exacerbated by combinational α-PD1 and α-CTLA4 therapy. To model RRD brain tumours specifically, we combined Pole S459F mice with conditional Msh2 knockout ( Msh2 LoxP ) and Nestin-cre mice. Nestin-cre + Msh2 LoxP/LoxP Pole S459F/+ mice rapidly succumbed to tumours between 8.6 and 12.4 weeks with 100% penetrance. Tumours developed in the cerebellum and histologically resembled human medulloblastoma. Importantly, tumours exhibited hallmark "ultrahypermutation" (~399 mutations/Mb) and analysis of mutational signatures revealed the presence of signature 14 (characteristic of combined MMR and POLE -proofreading loss). These tumours are transplantable and grow efficiently in syngeneic animals despite their high mutational load and presumed immunogenicity. This first mouse model of immunocompetent, hypermutant brain tumors can be used to uncover unique characteristics of RRD tumour evolution and allow for immune based therapeutic preclinical testing. Experiments to assess combinational ICIs and other therapeutic interventions will be presented.